Hydrogen sulfide augments synaptic neurotransmission in the nucleus of the solitary tract - Austgen, James R. (American Physiological Society, 2011)
Within the brain stem, the nucleus tractus solitarii (NTS) serves as a principal central site for sensory afferent integration from the cardiovascular and respiratory reflexes. Neuronal activity and synaptic transmission in the NTS are highly pliable and subject to neuromodulation. In the central nervous system, hydrogen sulfide (H(2)S) is a gasotransmitter generated primarily by the enzyme cystathionine-β-synthase (CBS). We sought to determine the role of H(2)S, and its generation by CBS, in NTS excitability. Real-time RT-PCR, immunoblot, and immunohistochemistry analysis identified the presence of CBS in the NTS. Patch-clamp electrophysiology in brain stem slices examined excitatory postsynaptic currents (EPSCs) and membrane properties in monosynaptically driven NTS neurons. Confocal imaging of labeled afferent synaptic terminals in NTS slices monitored intracellular calcium. Exogenous H(2)S significantly increased the amplitude of evoked solitary tract (TS)-EPSCs, frequency of miniature (m)EPSCs, and presynaptic terminal calcium fluorescence in the NTS. H(2)S did not alter action potential discharge or postsynaptic properties. On the other hand, the CBS inhibitor aminooxyacetate (AOA) significantly reduced the amplitude of TS-EPSCs and presynaptic terminal calcium fluorescence in the NTS without altering postsynaptic properties. Taken together, these data support a presynaptic role for endogenous H(2)S in modulation of excitatory neurotransmission in the NTS.